The 4‐Hole‐Board Test for Assessment of Long‐Term Spatial Memory in Mice. Issue 8 (25th August 2021) - d'Isa, Raffaele; Comi, Giancarlo; Leocani, Letizia
Abstract: The hole‐board test has been used in rodents since the early 60s to measure exploratory behavior, locomotor activity and cognitive function. The test is based on rodents' natural curiosity and attraction for novelty. Basically, the hole‐board consists of a small square arena with an extractable platform as floor, which has a set of equally spaced circular holes on its surface. In this article, we describe the protocol of a 4‐hole‐board test allowing the assessment of long‐term spatial memory in mice without the employment of water or food restriction, painful stimuli (as electrical shocks) or any aversive condition (as forced swimming or exposure to intense light). Four holes are present on the floor of the square arena (one for each of its four quadrants). Mice released in the arena spontaneously approach the holes and explore them by briefly inserting the snout inside, a behavior defined as nose‐poking (or head‐dipping). If, after 24 hr, rodents are re‐exposed to the hole‐board, the novelty of the holes decreases. Animals with an intact long‐term memory will show a reduction of the frequency of nose‐poking into the holes. The total number of nose‐pokes on day 1 is an index of exploration, while the percentage of decrease in nose‐poking on day 2 represents an index of long‐term spatial memory. Number of quadrant crossings is scored as a control measure for locomotor activity, which with the present protocol should remain stable across the days of testing. Indeed, the 4‐hole‐board test represents a stress‐free and animal‐friendly option to evaluate long‐term spatial memory. In the present paper, we provide detailed description of the hole‐board apparatus and step‐by‐step protocol for assessment of spatial memory in mice. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Validation of the 4‐hole‐board Basic Protocol 2 : Evaluation of long‐term spatial memory through the 4‐hole‐board test